(untitled) (Journal Of Educational and Psychological Researches, 2022)
The research aims to identify the bedroom furniture designs for children who are in ages range between (4-6) years and the rate of employing them in developing their aesthetic sense. To achieve this objective, the researchers developed the two research tools represented by a analysis-description form of bedroom furniture designs included a number of domains that were represented in the shapes, colors, and sizes of the furniture, as well as the availability of the safety factor, ease of use, cleaning and movement. As for the aesthetic sense scale included (30) paragraphs and alternatives (always, sometimes, never), they were distributed among a representative sample of (170) mothers of children were chosen randomly from (17) kindergartens from the in the city of Baghdad. The two researchers reached that Most of children have aesthetic sense. Most of the children’s bedroom furniture through its colors contributed to the development of their aesthetic sense. Most of the children’s bedroom furniture through its shapes played a positive role in developing their aesthetic sense. The sizes of most children’s bedroom furniture did not have a role in developing their aesthetic sense. The effect of both the ease of using and cleaning children’s bedroom furniture positively affects their aesthetic sense, as is the case with regard to ease of movement. According to these results, the researchers offered a number of recommendations and suggestions.